PENGARUH LINGKUNGAN RUMAH DAN PERILAKU MASYARAKAT DENGAN KEJADIAN PENYAKIT DEMAM BERDARAH DENGUE (DBD) DI KOTA PEKANBARU - Debby Febriani; Yusni Ikhwan Siregar; Zahtamal Zahtamal (Program Pascasarjana Universitas Riau, 2018)
The high number of dengue fever incident in Pekanbaru was because of many factors that affecting it. Among those factors, behavior factor and environment factor were two of them. This study aimed to analyze the correlation among home environment, the 3M plus behavior, and the household income of the dengue fever incident, also to analyze the most dominant factors. The type of the study was quantitative with the case control study approach. The study was done from January to March 2019 located in Pekanbaru.The population of the study were all the patients with dengue fever in January to march 2019based on the medical data record of Arifin Achmad hospital with the sample were 28 cases and 28 controls. Data were analyzed using chi-square and logistic regression. The results showed that the home environment variable which affecting the dengue fever incident was the exposure (p value=0,000), temperature (p value=0,001), moisture (p value=0,000), the existence of mosquito larvae (p value=0,032). The 3M behavior and the household income also have a relationship with the incident of dengue fever. The most dominant variable in the incident of dengue fever was temperature with OR 20,7. Environment, (exposure, temperature, moisture and the existence of mosquito larvae, 3M plus behavior and the household income were in the relation with dengue fever. The most dominant factor of dengue fever was temperature.